2015
DOI: 10.1038/srep11408
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling a molecular determinant for clathrin-independent internalization of the M2 muscarinic acetylcholine receptor

Abstract: Endocytosis and postendocytic sorting of G-protein-coupled receptors (GPCRs) is important for the regulation of both their cell surface density and signaling profile. Unlike the mechanisms of clathrin-dependent endocytosis (CDE), the mechanisms underlying the control of GPCR signaling by clathrin-independent endocytosis (CIE) remain largely unknown. Among the muscarinic acetylcholine receptors (mAChRs), the M4 mAChR undergoes CDE and recycling, whereas the M2 mAChR is internalized through CIE and targeted to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Thus, we speculate that hTAC internalizes via both the CDE and CIE pathways. This complicated endocytosis mechanism involving internationalization via multiple pathways not only occurs in hTAC but also in other PM proteins, including muscarinic acetylcholine receptor 4 (Boucrot et al, 2015 ; Wan et al, 2015 ), platelet-derived growth factor receptor β (Jastrzebski et al, 2017 ) and EGFR (Boucrot et al, 2015 ; Caldieri et al, 2017 ). Altogether, these results and our findings expand our understanding of the endocytic characteristics of certain PM protein cargoes.…”
mentioning
confidence: 99%
“…Thus, we speculate that hTAC internalizes via both the CDE and CIE pathways. This complicated endocytosis mechanism involving internationalization via multiple pathways not only occurs in hTAC but also in other PM proteins, including muscarinic acetylcholine receptor 4 (Boucrot et al, 2015 ; Wan et al, 2015 ), platelet-derived growth factor receptor β (Jastrzebski et al, 2017 ) and EGFR (Boucrot et al, 2015 ; Caldieri et al, 2017 ). Altogether, these results and our findings expand our understanding of the endocytic characteristics of certain PM protein cargoes.…”
mentioning
confidence: 99%
“…Internalization and recycling is essential for receptor resensitization after attenuation of the cellular response by increased/prolonged agonist exposure; thus enhanced abundance of those complexes is in accordance with increased M3 protein expression in IC/BPS disease. In contrast, the M2 is thought to be internalized via a clathrin‐independent endocytosis pathway and then targeted to lysosomes for degradation . Delaney et al suggested that once M2 mAChRs are initially internalized via clathrin‐independent endocytosis, they are quickly transferred to early endosomes of the clathrin endocytotic pathway in cultured HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…M1, M3, and M4 all undergo internalization via clathrin‐mediated endocytosis in a dynamin‐dependent manner . In contrast, several observations indicate that M2 mAChRs internalize via a poorly characterized clathrin‐independent endocytotic pathway . Even it is evident that clathrin is not involved in M2 endocytosis, the involvement of caveolin (Cav) and the GTPase dynamin could not be finally clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that m2R internalization pathway involves CCP only ( Pals-Rylaarsdam et al, 1997 ; Jones et al, 2006 ; Yamanushi et al, 2007 ). Other claimed that m2R is internalized through a clathrin-independent process ( Vogler et al, 1999 ; Delaney et al, 2002 ; Wan et al, 2015 ). Ockenga and Tikkanen (2015) propose that m2R endocytosis takes place by means of an atypical clathrin-mediated pathway that may involve a specific subset of CCP.…”
Section: Discussionmentioning
confidence: 99%